A Compact Multiband Notch UWB Antenna. (20th December 2012) - Kumar, K.; Gunasekaran, N.
Abstract : A simple and a compact coplanar waveguide (CPW) ultrawide band (UWB) antenna is presented. Multiband stop function is achieved by two different types of band stop resonators. One is a tilted square spiral slot resonator of different size and length etched on the patch and the other is a coupled resonator etched on the ground plane. These resonators provide considerable increase in notch bandwidth at the stop bands. The proposed antenna has a total size of 18 × 20.3 mm 2 . The designed antenna achieves pass band performance at 1.8–2.1 GHz (15.38%), 3.0–3.2 GHz (6.45%), 4.4–4.7 GHz (6.59%), 6.3-6.4 GHz (1.57%), and 8–11.2 GHz (33.33%) where VSWR <2 and four stop bands at 2.4–2.8 GHz (15.38%), 3.2–3.7 GHz (14.49%), 5.5–6 GHz (8.69%), and 6.5–7 GHz (7.40%) where VSWR is equal to 10. The antenna has a peak gain of 3.8 dBi. The measured results show that the antenna achieves good impedance matching and consistent radiation patterns over an operating bandwidth.